A Survey on Analysis of Online Consumer Behaviour Using Association Rules - M.R. Narasingha Rao, Dr; V.L Sita Ratnam, K; D.S. Prasanth, M; Lakshmi Bhavani, P (International Journal of Engineering and Technology, 2018)
In vogue the competitive world is searching for customer oriented approach. In order to accomplish that customer relation management (CRM) provides the services which meet the customer requirement. The requirements of a customer are collected in the form of data which is to be analyzed for obtaining customer behavior. Therefore inquiry is made to determine the characteristic features of a customer by using the data which is collected from different sources of all the online shopping sites. Data mining is a process of extracting useful information from the historical data. In this analysis the data of a online shopping website which is take from mechanical sector is tested by using some data mining algorithms like Apriori, FP-growth and Eclat algorithm of association rule mining. As a result of the study it is aimed to obtain frequent items purchased by the consumer by using the association results.Â